Effective Use of Data-Driven Digital Marketing For Digital Financial Services In Ghana - Abaidoo, Amos William (Global journal of Business and Integral Security, 2024)
Traditional banking behaviours are undergoing a paradigm shift, with customers leaning now more than ever towards the use of digital platforms for most, if not all financial transactions. Any form of friction, which inhibits customers from easily achieving their goals, is deemed unacceptable especially with high-expectations of instant gratification. Known to practicing data marketers, alongside the opportunities presented by Data- Driven Marketing, are the inherent challenges including decision making. The goal of this study is to gain a deep empirical understanding of what motivates and drives customer behaviour around digital banking and the specific path to take to make Data-Driven Digital Marketing achieve the desired results for Digital Financial Services Marketers in Ghana.